2020
DOI: 10.1002/pbc.28761
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve early detection of childhood cancer in low‐ and middle‐income countries: A systematic review

Abstract: Background: Childhood cancer outcomes in low-and middle-income countries (LMICs) lag behind those in high-income countries (HICs), in part due to late presentation and diagnosis. Though several interventions targeting early detection of childhood cancer have been implemented in LMICs, little is known about their efficacy. Methods: We conducted a systematic review to identify studies describing such interventions. We searched multiple databases from inception to December 4, 2019. Studies were included if they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
(184 reference statements)
0
6
0
Order By: Relevance
“…Across LMICs, a few HCW-focused training interventions aimed at improving pediatric cancer early recognition and referrals have been implemented, as documented in a recent systematic review. 24 Although some of these studies report important quantitative metrics such as increases in knowledge after intervention and increased number of referral and diagnosis, 21,[25][26][27] a detailed evaluation of these HCW-focused training interventions has been lacking. Our study addresses this research gap by providing information on the range of factors that should be considered when implementing a training intervention in an LMIC context, to ensure that the intervention achieves its desired impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Across LMICs, a few HCW-focused training interventions aimed at improving pediatric cancer early recognition and referrals have been implemented, as documented in a recent systematic review. 24 Although some of these studies report important quantitative metrics such as increases in knowledge after intervention and increased number of referral and diagnosis, 21,[25][26][27] a detailed evaluation of these HCW-focused training interventions has been lacking. Our study addresses this research gap by providing information on the range of factors that should be considered when implementing a training intervention in an LMIC context, to ensure that the intervention achieves its desired impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations addressed, in part, economic consequences for the society, such as the loss of the workforce and the costs for outcomes (rehabilitation, long-term complications, survivorship issues, etc.). For example, the costs and cost-effectiveness of treating childhood cancers in LMICs [17] in terms of disability-adjusted life years (DALY), survival and countryspecific life expectancy were recently compared with GDP products using the Consolidated Health Economic Evaluation Reporting Standards, although the identified body of evidence for these countries was still low and had high risks of bias, and true treatment costs were likely underestimated, Fung et al [17] and Zabih et al [18] concluded that overall childhood cancer treatment appears to be clinically effective and cost effective in LMICs, making sufficient cancer care achievable for these patients. Economic hardship reported by a third of families, including an inability to pay drugs (45%), mortgages (18%), utilities (12%); 28% taking personal loans; 20% selling assets.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, scale-up strategies are necessary to diagnose and treat these additional patients. Although no effective interventions for the early diagnosis of children have been reported [ 22 ], several work streams could be prioritised such as conducting targeted awareness campaigns, improving referral pathways, mitigating financial hardships, establishing follow-up mechanisms to minimise abandonment and capacity building on both the facility and the personnel levels. Additionally, diagnosing more patients will be associated with higher upfront costs, to establish facilities, train and hire personnel and procure additional medicines and supplies.…”
Section: Discussionmentioning
confidence: 99%